A study of coagulase-negative staphylococci (CoNS) isolated from bovine mastitis for the presence of penicillin and methicillin resistance-encoding genes in the north west of Iran - Dastmalchi Saei, H.; Hossein-zadeh, S. (Archives of Razi Institute, 2014)
Coagulase-negative staphylococci (CoNS) are often associated with bovine mastitis and may be resistant to antimicrobial therapy. The aim of the current study was to investigate the presence of blaZ (responsible for penicillin resistance) and mecA (responsible for methicillin resistance) genes among 108 CoNS belonging to 9 different species isolated from bovine mastitis in seven dairy herds (H1-H7). Of 108 CoNS isolates, 44 were Staphylococcus haemolyticus, 17 S. chromogenes, 11 S. epidermidis, 11 S. warneri, 11 S. cohnii, 6 S. simulans, 4 S. hominis, 3 S. capitis, and 1 S. xylosus. The blaZ was detected in 65.7% (n=71) of all Staphylococcus spp. isolates. Five isolates were positive for the presence of mecA gene (4.6%), including 2 S. hominis, 1 S. haemolyticus, 1 S. epidermidis, and 1 S. warneri. All mecA-carrying CoNS were also positive for the blaZ gene and were recovered from two studied herds (H3 and H6). Some variations were also observed in distribution of both blaZ and mecA genes between CoNS species. This study demonstrates that CoNS from bovine mastitis can be reservoirs of blaZ gene. This study also provides evidence of the presence of methicillin resistant CoNS (MR-CoNS) and emphasizes the need for their epidemiological monitoring, in order to prevent the risk of spread to human through direct contact and/or consumption of contaminated food.